Bioaccumulation of PCBs, OCPs and PBDEs in Marine Mammals From West Antarctica - Khairy, Mohammed; Brault, Emily; Dickhut, Rebecca; Harding, Karin C.; Harkonen, Tero; Karlsson, Olle; Lehnert, Kristina; Teilmann, Jonas; Lohmann, Rainer (Frontiers in Marine Science, 2021)
To understand the bioaccumulation and food web dynamics of persistent organic pollutants (POPs) as a function of species, age and sex in Antarctic mammals, blubber samples of 3 killer whales (Type C) and 77 pinnipeds (Weddell, Ross and crabeater seals) were collected from the Southern Ocean, Antarctica. They were analyzed for polychlorinated biphenyls (PCBs), organochlorine pesticides (OCPs) and polybrominated diphenyl ethers (PBDEs). ∑DDTs, ∑29PCBs and chlordanes (12 – 4,600, 13 – 1,600 and <1.5 – 1,700 ng/g lipid respectively) were the most abundant POPs. Except for PBDE the killer whale had on average several times higher levels of POPs compared to the seals. PCBs and PBDEs were consistently higher in adult crabeater and Weddell seal males, and in adult female Ross seals than in other sex and age groups reflecting an age accumulation and possible influence of segregated diet, foraging areas, and metabolic transformation rates. POPs concentrations significantly correlated with gene transcription of nuclear receptors involved in detoxification of contaminants and immune relevant cell mediators in the crabeater seals, indicating possible immunotoxic and deleterious health effects. This represents one of the largest studies on POPs in Antarctic marine predators and highlights the complexity of POPs bioaccumulation.